Pengaruh Right Issue Terhadap Likuiditas Saham Dan Abnormal Return Pada Saham Syariah Periode 2021-2023 - Albab Rahmatya, Ulil; Adetio Setiawan, Romi; Afrida Indra, Yetti (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study aims to determine whether a right issue can affect stock liquidity and abnormal returns. The object of this study is a company listed on the Indonesian Sharia Stock Index that conducts a right issue. The type of research is quantitative. The sampling technique uses the purposive sampling method, obtained the number of samples that meet the criteria as a research sample of 15 companies that conducted a right issue in 2021-2023. The data used is secondary data in the form of the number of shares distributed in the right issue, stock prices, IDX composite. stock trading volume, and the number of shares outstanding before and after the announcement of the right issue. The method used in this study is event study. The data analysis technique was carried out using the structural equation modeling partial least square (SEM-PLS) method. Based on the tests that have been carried out, it shows that there is no significant effect of the implementation of the right issue on stock liquidity and abnormal returns on Islamic stocks in the 2021-2023 Islamic Stock Index.